2008
DOI: 10.1063/1.3021141
|View full text |Cite
|
Sign up to set email alerts
|

Composition dependence of field induced anisotropy in ferromagnetic (Co,Fe)89Zr7B4 and (Co,Fe)88Zr7B4Cu1 amorphous and nanocrystalline ribbons

Abstract: The composition dependence of field induced anisotropy KU of field annealed soft ferromagnetic (Co1−xFex)89Zr7B4 and (Co1−xFex)88Zr7B4Cu1 amorphous and amorphous/nanocrystalline “nanocomposite” melt spun ribbons is investigated. With the exception of the highest Co-containing alloys (x<∼0.10), the observations are discussed in terms of a superposition of directional pair ordering of Fe,Co atoms and an additional contribution presumably due to the presence of Zr and B in both the field crystallized and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
29
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…This composition has a high Curie temperature compared to Fe-based amorphous alloys 11 and is responsive to field annealing. 12 We find a large enhancement of the GMI ratio and g in the Co-coated ribbons, both being largest in the sample with Co coated on the free ribbon surface. It is shown that the presence of the Co coating layer not only reduces stray fields due to surface irregularities, but also closes up the magnetic flux path, both of which contribute to the enhanced GMI effect in the Co-coated ribbons.…”
mentioning
confidence: 75%
“…This composition has a high Curie temperature compared to Fe-based amorphous alloys 11 and is responsive to field annealing. 12 We find a large enhancement of the GMI ratio and g in the Co-coated ribbons, both being largest in the sample with Co coated on the free ribbon surface. It is shown that the presence of the Co coating layer not only reduces stray fields due to surface irregularities, but also closes up the magnetic flux path, both of which contribute to the enhanced GMI effect in the Co-coated ribbons.…”
mentioning
confidence: 75%
“…A new class of Fe-Co-based amorphous and nanocomposite materials, HiTperms, [6][7][8][9][10][11][12] show promise for high frequency applications. Low losses, tunable anisotropies, and robust mechanical properties suggest their use in high efficiency, high speed motors both at room temperature and operating temperatures >300 C. For motors where material strength is critical, Co-rich compositions offer good soft magnetic properties without the brittleness found in Fe-rich alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Recent suppression of the nucleation of the c-phase has been observed in Co-Fe-based nanocomposites at compositions where the binary Fe-Co phase diagram predict that the a-andcphases coexist. [3][4][5][6][7][8] In Fe-Ni-based nanocomposites, similar observations in Fe-rich alloys 11 show nucleation of the c-phase is suppressed in favor of a metastable a-phase.…”
Section: Introductionmentioning
confidence: 59%
“…2 Fe-based alloys have attracted the most attention, as optimized alloys exhibit relatively high magnetic flux densities and low losses. Co-based alloys, with small or zero magnetostriction, a relatively large response to magnetic field annealing [3][4][5][6][7][8] and excellent mechanical properties making them interesting for magnetic sensors and high frequency applications. 9,10 In transforming amorphous precursors to nanocomposite magnets, it is possible to suppress stable phase formation and exploit properties of metastable phases.…”
Section: Introductionmentioning
confidence: 99%